Tren Penelitian Penggunaan Artificial Intelligence dalam Manajemen Pemasaran Digital: Kajian Bibliometric Vosviewers - Denok Mugi Hidayanti; Jhoni Susanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
With all this progress, new challenges arise related to data privacy, marketing ethics, and sustainability. Regulations such as GDPR (General Data Protection Regulation) require companies to be more careful in managing customer data, while consumers increasingly expect responsible and environmentally friendly marketing practices. This research aims to explore the latest trends in digital marketing management, analyze their impact on marketing strategies, and identify the challenges and opportunities faced by marketers in this digital era. This research uses a bibliometric approach to analyze research trends in digital marketing management. This approach allows researchers to identify publication patterns, main themes, and relationships between various concepts in the relevant scientific literature. Data sources for this research were collected from leading scientific databases such as Google Scholar. Trends in the use of Artificial Intelligence in digital marketing management with the help of Vosviewers media show that research is still open regarding studies related to marketing, participation, illusion, implementation, paramount importance, and business customers.